2019
DOI: 10.1002/uog.20147
|View full text |Cite|
|
Sign up to set email alerts
|

Does exercise during pregnancy impact on maternal weight gain and fetal cardiac function? A randomized controlled trial

Abstract: Objective To evaluate the association between physical exercise during pregnancy and maternal gestational weight gain and fetal cardiac function. Methods This was a randomized controlled trial of women with a singleton pregnancy managed from the first trimester at the Hospital de Torrejón, Madrid, between November 2014 and June 2015. Women were randomized to either follow a supervised physical conditioning program, consisting of a 60‐min session 3 days per week for the duration of pregnancy, or not attend any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 38 publications
0
48
0
3
Order By: Relevance
“…However, in many published reports, information on the intervention compliance is not available . In a recently published trial from our group, the compliance rate in the intervention group was 56% …”
Section: Univariate and Multivariate Analysis For Predictive Factors mentioning
confidence: 86%
“…However, in many published reports, information on the intervention compliance is not available . In a recently published trial from our group, the compliance rate in the intervention group was 56% …”
Section: Univariate and Multivariate Analysis For Predictive Factors mentioning
confidence: 86%
“…Given that informal literature reviews are frequently found to be selective and avoid contradictory studies, the gold standard for this process should be performing a formal systematic review prior to embarking on a new trial. Of three new trials of therapeutic interventions in obstetrics published in this journal last year, all made reference to prior work in their field but only one referred to a systematic review of the literature on the topic. Even in this study, the systematic review mentioned was published after the trial recruitment had ended, so clearly it was not used to inform the trial design.…”
Section: The Problem Of Research Waste In Obstetricsmentioning
confidence: 99%
“…9,16,17 Additionally, passive swinging associated with dancing during pregnancy could potentially increase the heart rate of the fetus as well as fetal movement. 33 Because there have been controversial findings regarding the effect of exercise on fetal cardiac function during pregnancy, 34 the potential for fetal stress during the implementation of dancing during labor should be acknowledged. 34 Interestingly, along with potential unknown physical implications, there is a potential role in the development of the fetus's future personality and talents.…”
Section: Other Considerationsmentioning
confidence: 99%
“…33 Because there have been controversial findings regarding the effect of exercise on fetal cardiac function during pregnancy, 34 the potential for fetal stress during the implementation of dancing during labor should be acknowledged. 34 Interestingly, along with potential unknown physical implications, there is a potential role in the development of the fetus's future personality and talents. 33 A survey study of professional dancers identified that mothers who danced throughout their pregnancy were more likely to have children who needed to be rocked to sleep during the first year of life and were more likely to play a musical instrument.…”
Section: Other Considerationsmentioning
confidence: 99%